A need-supportive teaching approach among students with intellectual disability in physical education. (May 2022) - Behzadnia, Behzad; Rezaei, Fahimeh; Salehi, Maryam
Abstract: Objectives: The present study tested a need-supportive teaching approach to enhance the experience of need satisfaction, autonomous motivation, and well-being, and to decrease need frustration, controlled motivation, amotivation, and ill-being among students with intellectual disability in physical education activities. We further tested the effects of experimental condition in predicting students' need satisfaction and need frustration, motivational regulations, and well-being and ill-being over the semester. Design: Experimental study. Methods: Ninety eight students with mild and borderline intellectual disabilities ( M age = 16.53, SD = 3.22; female = 63.3%) attended in this experimental semester-long study. Teachers ( N = 6) of students randomly assigned into either an experimental (need-supportive teaching style) or a control (usual teaching style) condition. Students filled out the targeted questionnaires at the beginning (T1), middle (T2), and the end of the semester (T3). Findings: The results showed that students of the teachers in the experimental condition reported higher need satisfaction and positive affect, and lesser need frustration, amotivation, and negative affect than students of the teachers in the control condition. The results also showed that experimental condition predicted positively T3 need satisfaction, whereas and negatively predicted T3 need frustration, amotivation, and negative affect. Conclusion: Findings highlight the importance of teachers' need-supportive teaching behaviors to enhance positive outcomes, and decreasing their negative outcomes in students with intellectual disabilities in PE. Highlights: We implemented a need-supportive teaching approach in students with intellectual disabilities in physical education. The need-supportive teaching approach positively predicted T3 need satisfaction. The need-supportive teaching negatively predicted T2 and T3 need frustration, T2 and T3 amotivation, and T3 negative affect. The need-supportive intervention increased students' need satisfaction, and decreased need frustration, amotivation, and negative affect. Need frustration and negative affect increased, and positive affect decreased in the control condition over a semester.